2014
DOI: 10.3109/15412555.2013.813448
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risk Factors for COPD Phenotypes in the Multi-Ethnic Study of Atherosclerosis (MESA) Lung Study

Abstract: Introduction The contribution of occupational exposure to the risk of chronic obstructive pulmonary disease COPD in population-based studies is of interest. We compared the performance of self-reported exposure to a newly developed JEM in exposure-response evaluation. Methods We used cross-sectional data from Multi-Ethnic Study of Atherosclerosis (MESA), a population-based sample of 45–84 year olds free of clinical cardiovascular disease at baseline. MESA ascertained the most recent job and employment, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 29 publications
1
37
0
4
Order By: Relevance
“…1 Epidemiological studies of COPD use a variety of methods to assign estimates of occupational exposure levels. [1][2][3] These methods include a National Institute for Occupational Safety and Health COPD-specific job exposure matrix (NIOSH COPD JEM) previously constructed by three NIOSH industrial hygienists (IHs). 2 3 The NIOSH COPD JEM was developed to be a generalisable tool to assess COPD risk by assigning exposure levels to all US Census 2000 Occupations regardless of disease status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Epidemiological studies of COPD use a variety of methods to assign estimates of occupational exposure levels. [1][2][3] These methods include a National Institute for Occupational Safety and Health COPD-specific job exposure matrix (NIOSH COPD JEM) previously constructed by three NIOSH industrial hygienists (IHs). 2 3 The NIOSH COPD JEM was developed to be a generalisable tool to assess COPD risk by assigning exposure levels to all US Census 2000 Occupations regardless of disease status.…”
Section: Introductionmentioning
confidence: 99%
“…In earlier work, we found that occupational dust exposures ascertained by this JEM were associated with spirometry-defined COPD. 2 This study further examined the usefulness of the COPD JEM by comparing COPD JEM-assigned occupational exposures with those assigned by expert evaluation of detailed, occupation, industry and job task information for a variety of jobs held by members of an integrated health plan in the Northwest USA.…”
Section: Introductionmentioning
confidence: 99%
“…The extraordinary array of data provided by contemporary cohorts of COPD opens a window to new research questions, as demonstrated by Paulin and colleagues. Gray areas in need of further exploration, which could be developed using these data, include the role of early small airway involvement, the differences in disease progression according to exposure history, clinical and imaging phenotypes of occupational COPD, sex differences, and genetic interactions as determinants of outcomes and disease (16)(17)(18)(19).…”
Section: Causality Established Time To Focus On Effect and Phenotypesmentioning
confidence: 99%
“…Присутствие различных ком-понентов в промышленном аэрозоле, их ком-плексное воздействие на органы дыхания в со-четании с многочисленными факторами экзо-и эндогенного характера в условиях различных производств приводят к разнообразию клини-ческих проявлений профессионального брон-хита [1,13,15,18].…”
unclassified